Study on Relationship between Roles of Public Open Spaces and Pedestrians Inside Campus: Case Studies from Universities in Thailand and Hungary - Kongphunphin, Chompoonut; Hegyi, Pál; Koren, Csaba (Acta Technica Jaurinensis, 2020)
Public open spaces in campuses are social places for students and staffs. Convenient accessibility both physical and visual is the main factor that attracts people to use these spaces. This article analyses the physical layout of public open spaces through their relationship with the surrounding. The purpose of this study is to compare the relationship between public open spaces and pedestrians in the campuses. The case study conducted in four campuses located in Thailand and Hungary. In order to get the required data, spatial analysis from Geographic Information System and observation survey was employed as qualitative techniques. The study revealed that pedestrian facilities are the most important accessibility types in public open spaces in each campus. The different lengths of pedestrian facilities are related with three factors of campuses’ layout. They are the size, surrounding and design elements of the campuses and their public open spaces.